Acompañamiento Parental y Proceso de Enseñanza-Aprendizaje en los niños del Nivel Inicial I del Centro de Desarrollo Infantil María Angelica Idrovo. Periodo 2023-2024 - Sarmiento Moncada., Diana Carolina (2024)
Parental accompaniment is key in the teaching-learning process of children, especially in early education. The present research had an objective to analyze the level of parental accompaniment and its relationship with the teaching-learning process of children in early level I at the María Angelica Idrovo Early Childhood Center. A qualitative approach with descriptive design was used, using observation and interview techniques, the sample included 18 students and 1 teacher of preschool level I. The results show a limited participation of parents in school activities and monitoring of their children's learning. It can be mentioned that the teaching-learning process is dynamic and playful, but it is affected due the lack of continuity and attention from parents. An important relationship was found between the level of parental accompaniment and the teaching-learning process of the children, this research highlights the importance of collaboration between the school and the family to improve the integral development of the students. It is evident that children with greater parental support showed better adaptation to the school environment and more notable progress in their development. The research also identified challenges in the implementation of strategies to encourage parental involvement, such as lack of time and resources. It is concluded that greater parental involvement is positively related to a better teaching-learning process and comprehensive development of children. It is suggested that comprehensive parental involvement programs be implemented, such as training workshops for parents and activities that actively involve families in the educational process. In addition, it is recommended to establish more effective communication means between teachers and parents and to design strategies that reinforce the link between the home and the educational center to improve the teaching-learning process at the initial level. Key words: Accompaniment, Process, early education, family participation, child development.